Look into my eyes: Pupillometry reveals that a post‐hypnotic suggestion for word blindness reduces Stroop interference by marshalling greater effortful control. (28th January 2021) - Parris, Benjamin A.; Hasshim, Nabil; Dienes, Zoltan
Abstract: The mechanisms underpinning the apparently remarkable levels of cognitive and behavioural control following hypnosis and hypnotic suggestion are poorly understood. Numerous independent studies have reported that Stroop interference can be reduced following a post‐hypnotic suggestion that asks participants to perceive words as if made up of characters from a foreign language. This effect indicates that frontal executive functions can be more potent than is generally accepted and has been described as resulting from top‐down control not normally voluntarily available. We employed eye tracking and pupillometry to investigate whether the effect results from voluntary visuo‐attentional strategies (subtly looking away from the word to prevent optimal word processing), reduced response conflict but not overall conflict, Stroop effects being pushed from response selection to response execution (response durations) or increased proactive effortful control given enhanced contextual motivation (as indexed via pupil dilation). We replicated the reduction in Stroop interference following the suggestion despite removing any trials on which eye movements were not consistent with optimal word processing. Our data were inconclusive with regards to conflict type affected by the suggestion in the latency data, although preserved semantic conflict was evident in the pupil data. There was also no evidence of Stroop effects on response durations. However, we show that baseline‐corrected pupil sizes were larger following the suggestion indicating the socio‐cognitive context and experimental demands motivate participants to marshal greater effortful control. Abstract : We investigated the mechanisms underpinning an apparently remarkable level of cognitive control in which the normally robust Stroop interference effect is substantially reduced following a post‐hypnotic suggestion for a blindness to word meaning. We employed eye tracking and pupillometry to test accounts of this effect that are not based on the operation of a special control mechanism. We show that baseline‐corrected pupil sizes are larger following the word blindness suggestion, indicating that the socio‐cognitive context and experimental demands motivate participants to marshal greater effortful control.